2013
DOI: 10.1186/1939-8433-6-3
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity of arsenic accumulation in rice and QTL analysis of methylated arsenic in rice grains

Abstract: BackgroundRice is a major source of dietary intake of arsenic (As) for the populations that consume rice as a staple food. Therefore, it is necessary to reduce the As concentration in rice to avoid the potential risk to human health. In this study, the genetic diversity in As accumulation and As speciation in rice grains was investigated using a world rice core collection (WRC) comprising 69 accessions grown over a 3-year period. Moreover, quantitative trait locus (QTL) analysis was conducted to identify QTLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 34 publications
2
44
0
2
Order By: Relevance
“…There have been a number of field studies on the genotypic variations of As and Cd concentrations in rice grain (Norton et al 2009; 2012a; Kuramata et al, 2013; Pinson et al, 2015). However, most of these studies tested rice germplasm resources, and those accessions found to have low levels of As or Cd accumulation may not be suitable to the growth conditions in South China, where the problem of heavy metal and metalloid contamination is serious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of field studies on the genotypic variations of As and Cd concentrations in rice grain (Norton et al 2009; 2012a; Kuramata et al, 2013; Pinson et al, 2015). However, most of these studies tested rice germplasm resources, and those accessions found to have low levels of As or Cd accumulation may not be suitable to the growth conditions in South China, where the problem of heavy metal and metalloid contamination is serious.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoremdiation has been tested in small scale field trials (Murakami et al, 2009; Mandal et al, 2012; Deng et al, 2015), but its applicability to cleaning up large areas of contaminated paddy soils remains uncertain. Selection of cultivars accumulating low levels of Cd or As represents a feasible and practical option because there exist large genetic variations among rice cultivars in the accumulation of these metals and metalloids in grain (Norton et al, 2012a; Duan et al, 2012; Kuramata et al, 2013; Pinson et al 2015). For example, Norton et al (2012a) conducted six field trials in Bangladesh, China and USA over 2 years and found there was a 3–34 fold variation in grain As concentration among c. 300 rice accessions (Norton et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated significant variations in the level of As and Cd accumulation in crops. Among 69 World Rice Core Collection (WRC) accessions, a threefold difference in the total grain As concentration was observed between the lowest and highest cultivars [13]. The reported range of Cd concentrations in rice grains among 43 cultivars is 0.30-2.19 mg kg −1 when the plants are grown in soils contaminated with high levels of Cd [14].…”
Section: Introductionmentioning
confidence: 97%
“…In plants, arsenic tolerance is critical for adaptation to specific soils and has determined plant distribution 4,5 ; the molecular mechanisms are analyzed mainly by studying proteins presumably involved in arsenate (As(V)) tolerance based on sequence homology with bacterial and yeast proteins 6,7 . Genetic approaches are little used to study As(V) tolerance mechanisms [8][9][10][11][12] , and the genes implicated in natural intraspecific variation are unknown [13][14][15] .…”
mentioning
confidence: 99%